Präpositionen mit doppelter Referenz im Polnischen und ihre Äquivalenz im Deutschen - Gaca, Alicja (Studia Germanica Posnaniensia, 2018)
In her analysis the author compares Polish spatial prepositions like zza, spod, which comprise two relations -that of position (status essivus) and that of motion (status lativus), with their German equivalents. The following issues are discussed: the ablative constructions and corresponding gaps in the spatial relations of Polish and German, the defectiveness of the preposition system and the equivalence in the domain of ablative relations, the rules of equivalence in this domain, which include the anaphora.